Michael Vey rise of the Elgen. (Michael Vey #2) - Evans, Richard Paul (New York Mercury Ink/Simon Pulse, 2012)
Fifteen-year-old Michael Vey, born with Tourette's syndrome and special electromagnetic powers, joins his techno-genius best friend and an alliance of other "electric" teenagers to battle powerful foes in the jungles of Peru, where Michael learns the Order of Elgen's plan to "restructure" the world
1
Keywords: Electricity -- Juvenile fiction; Tourette syndrome -- Juvenile fiction